Reuse of Treated Water From Bojongsoang Domestic Wastewater Treatment Installation as Water for Industrial Purposes - Budi Heri Pirngadi; Deden Syarifudin; Viera Mustika Octaviani (Department of Urban and Regional Planning, Diponegoro University, 2024)
Subdistrict Bojongsoang and its surroundings are based on the 2016-2036 Bandung Regency Spatial Planning, the designated area where the industry is. Currently, there are 125 existing industries operating. The area is also included in groundwater withdrawal through well artesian on a massive scale, including into the national protected area (CAT: Groundwater Basin) Bandung - Soreang Area. Excessive groundwater extraction poses challenges coupled with significant water demand from society and industry. This will result in deteriorated groundwater conditions that require prompt restoration, having already suffered damage. On the other hand, there is Bojongsoang WWTP, which can treat wastewater at 2800 l/s; meanwhile, at the moment, this capacity processing is utilized about 37-40% or about 100m3/day. This research uses a descriptive method. The research results prove that reusing water from Bojongsoang WWTP could produce raw water for the necessity industry of 300 l/s.